The Implementation Of Direct Reading-Thinking Activity (DR-TA) Strategy in Teaching Reading Comprehension at Eleventh Grade of SMAN 2 Sungai Limau - Annisa, Dyfa; Amiza, Elsi; Kardena, Absharini; Syahrul, Syahrul (Pusdikra-Publishing.com, 2025)
The aim of this study is to desccribe how the implementation of Direct Reading-Thingking (DR-TA) strategy implemented by the teacher in teaching reading comprehension and what challenges the teacher faced in adminitering this strategy in class. The informant in this research was one of the English teachers in class XI of SMAN 2 Sungai Limau. The data collection methods were observation and interview. Data collection was done through observation checklist and interview with the teacher. Observations were made in class XI MIPA 5 and class XI MIPA 6. Data analysis was done by data collection, data reduction, data presentation, and conclusion, the data was presented in descriptive qualitative format. The finding show that the teacher had implemented this strategy in teaching reading comprehension, but there was one step that was skipped by the teacher. The challenges that teachers face in the classroom when implementing the DR-TA strategy are firstly the limited time they have in class, while the time needed for the implementation of this strategy is long. Second, students who are not active and enthused in the learning process. The third is the limited background knowledge of students so that it is difficult to provide predictions.